Breast cancer statistics, 2013 - DeSantis, Carol; Ma, Jiemin; Bryan, Leah; Jemal, Ahmedin (CA: a cancer journal for clinicians, 2014)
In this article, the American Cancer Society provides an overview of female breast cancer statistics in the United States, including data on incidence, mortality, survival, and screening. Approximately 232,340 new cases of invasive breast cancer and 39,620 breast cancer deaths are expected to occur among US women in 2013. One in 8 women in the United States will develop breast cancer in her lifetime. Breast cancer incidence rates increased slightly among African American women; decreased among Hispanic women; and were stable among whites, Asian Americans/Pacific Islanders, and American Indians/Alaska Natives from 2006 to 2010. Historically, white women have had the highest breast cancer incidence rates among women aged 40 years and older; however, incidence rates are converging among white and African American women, particularly among women aged 50 years to 59 years. Incidence rates increased for estrogen receptor‐positive breast cancers in the youngest white women, Hispanic women aged 60 years to 69 years, and all but the oldest African American women. In contrast, estrogen receptor‐negative breast cancers declined among most age and racial/ethnic groups. These divergent trends may reflect etiologic heterogeneity and the differing effects of some factors, such as obesity and parity, on risk by tumor subtype. Since 1990, breast cancer death rates have dropped by 34% and this decrease was evident in all racial/ethnic groups except American Indians/Alaska Natives. Nevertheless, survival disparities persist by race/ethnicity, with African American women having the poorest breast cancer survival of any racial/ethnic group. Continued progress in the control of breast cancer will require sustained and increased efforts to provide high‐quality screening, diagnosis, and treatment to all segments of the population. CA Cancer J Clin 2014;64:52–62. © 2013 American Cancer Society, Inc.